2017
DOI: 10.5897/ajfs2017.1626
|View full text |Cite
|
Sign up to set email alerts
|

Bromatological analysis, phytochemical and antioxidant potential of carnauba (Copernicia prunifera (Mill.) H.E. Moore) fruit

Abstract: Chemical composition as well as phytochemicals and antioxidant activity of underutilized plants, such as carnauba palm (Copernicia prunifera), provide an informed decision on how to maximize their benefits. This study aimed to evaluate the chemical composition and antioxidant activity of the fruit of carnauba. The total phenolic content (gallic acid equivalents, GAE) of the ethanol extract of the whole fruit, pulp and kernel were 44.6000, 0.0447 and 0.6930 mg GAE/g extract, respectively. The respective total t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The resulting color, blue-black or green-black after the reaction, can be used to distinguish gallic tannins from catechic tannins. 31 Evaluation of the presence of saponins, steroids, and triterpenes Matos's methods 32 were employed to conduct screening for saponins, steroids, and triterpenes. In the saponins assessment, 0.3g of propolis extract was subjected to a 2-minute boil with 5 mL of distilled water, followed by shaking and a 3-minute rest.…”
Section: Evaluation Of the Presence Of Tanninsmentioning
confidence: 99%
“…The resulting color, blue-black or green-black after the reaction, can be used to distinguish gallic tannins from catechic tannins. 31 Evaluation of the presence of saponins, steroids, and triterpenes Matos's methods 32 were employed to conduct screening for saponins, steroids, and triterpenes. In the saponins assessment, 0.3g of propolis extract was subjected to a 2-minute boil with 5 mL of distilled water, followed by shaking and a 3-minute rest.…”
Section: Evaluation Of the Presence Of Tanninsmentioning
confidence: 99%
“…1,2 Although its fruit is generally used for animal feed, it is also used in human food due to its nutritional value. 3 Figure 1 should not only be a way of storing and marketing the fruit for a long period, but it should maintain the amount of the chemical composition found in the fresh fruit; however, studies have shown that processing techniques can drastically affect the chemical characteristics of the fruits. 4,5 Thus, the study of the influence of different technological processes (freezing and freeze-drying) on the bioactive compounds and antioxidant activity of carnauba pulp is relevant, as it assesses which losses can be suffered by vegetable raw materials after different processes, as well as whether these changes are significant and detract from the technology used, thus contributing to the expansion of a field of study of this little-explored fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Unripe fruits are greenish, and as they mature and ripen, they turn purple. 1 Bioactive compounds are presented in the fruit, such as phenolic compounds, anthocyanins, carotenoids, flavonoids, and vitamin C. 3 These substances intake is important, as they have antioxidant action and help the human body to fight free radicals, thus acting in the prevention of some diseases, contributing to the maintenance of the health of those who consume them. The chemical composition of the carnauba fruit is an important attraction for consumption, however, as the fruit is available only as fresh product, its consumption only occurs during the harvest period (January to April) and is therefore limited and seasonal.…”
Section: Introductionmentioning
confidence: 99%